2016
DOI: 10.1097/dad.0000000000000396
|View full text |Cite
|
Sign up to set email alerts
|

Study of Epithelial to Mesenchymal Transition in Atypical Fibroxanthoma and Undifferentiated Pleomorphic Sarcoma to Discern an Epithelial Origin

Abstract: Atypical fibroxanthoma (AFX) is considered a fibroblastic or myofibroblastic neoplasm probably corresponding to a superficial variant of undifferentiated pleomorphic sarcoma (UPS). However, an epithelial origin has also been postulated. An immunohistochemical study of the epithelial to mesenchymal transition (EMT) phenomenon was performed in a series of 19 AFX and 4 UPS to discern an epithelial origin. A panel of epithelial (cytokeratins AE1-AE3 panel, podoplanin D2-40, and E-cadherin) and EMT (vimentin, Twist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The differentiation between AFX and PDS is challenging since the tumors resemble each other both histopathologically and immunohistochemically. PDS is distinguished from AFX by features such as histological invasion of the subcutaneous tissue, vascular or perineural invasion, the presence of necrosis or local invasion/metastases 31,32 . The current consensus is that AFX does not metastasize 9,10 ; therefore, we chose to consider the cases of metastasis as a progression of the primary AFX diagnosis to a PDS.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation between AFX and PDS is challenging since the tumors resemble each other both histopathologically and immunohistochemically. PDS is distinguished from AFX by features such as histological invasion of the subcutaneous tissue, vascular or perineural invasion, the presence of necrosis or local invasion/metastases 31,32 . The current consensus is that AFX does not metastasize 9,10 ; therefore, we chose to consider the cases of metastasis as a progression of the primary AFX diagnosis to a PDS.…”
Section: Discussionmentioning
confidence: 99%
“…From the immunohistochemical point of view, we did not find a different profile among tumors with different cellular types. Toll and coworkers evaluated the immunohistochemical expression of EMT (epithelial to mesenchymal transition) markers in a series of AFX and PDS, concluding that EMT does not play a role in the development of these tumors 18 . On the contrary, a more recent study found that EMT is upregulated in AFX.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship of AFX and pleomorphic dermal sarcoma (PDS) is still not clearly identified (43). As AFX is a diagnosis of exclusion, it is mandatory to apply strict diagnostic criteria that include diligent immunohistochemical workup (812).…”
Section: Discussionmentioning
confidence: 99%
“…After its first description in 1963, much effort was spent to better understand the tumorigenesis and molecular biology of this tumor entity including immunohistochemical analyses, electron microscopy, comparative genomic hybridization and next generation sequencing (5,6). However, the pathogenesis of AFX is still unclear with keratinocytes, fibroblasts and myofibroblasts having been discussed as potential cells of origin (7,8). Since this tumor shows a highly heterogeneous histological structure with tumor cells ranging from spindle and epithelioid to multinucleated cells and a variably structured extracellular matrix, the histological diagnosis is challenging with undifferentiated pleomorphic sarcoma, malignant fibrous histiocytoma, dedifferentiated squamous cell carcinoma, dermatofibrosarcoma protuberance and leiomyosarcoma as differential diagnoses (1,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation